(untitled) (Journal of Information Technologies in Education (ITE), 2017)
By using MATLAB we demonstrate a variety of parametric curves of the family "Parametric Rose" (Rhodonea), characterized by four factors. The article is intended to encourage students to study the parametric curves. The values of coefficients affect the shape of the curve and its period.Changes with time one of the curve parameters makes the effect of animation. Different versions of coloring the curve increase the aesthetic impact on results. A beautiful MATLAB-program with Graphical User Interface (GUI) is suggested. It allows students to "play" with the curves on the computer screen and demonstrates amazing properties of the "Rose" parametric family depending on the values and the ratio of their coefficients. It may allow and teachers to inspire students by exploring these additional non-school materials. Students can see the beauty of mathematics and gain additional knowledge about parametric functions. From another side, the program provides an exercise example of algorithms and programming accessible for modern students. Animation of curves proposed can also serve as exercises both for mathematics and programming.